Pediatric Melanoma: Epidemiology, Pathogenesis, Diagnosis and Management - J. M. Neves; B. Duarte; M. J. Paiva Lopes (Sociedade Portuguesa de Dermatologia e Venereologia, 2020)
Pediatric melanoma is the most common skin cancer in children. However, it is extremely rare this population, being even rarer in younger than 10 years of age. Its diagnosis is often difficult, due to its rarity and atypical presentations. There are three main subtypes of pediatric melanoma: Spitzoid melanoma, melanoma arising in a congenital melanocytic nevus and conventional melanoma. Congenital melanomas exist and are exceptionally rare, although they do not constitute a different subtype of melanoma. Spitzoid melanoma is the most common subtype affecting children younger than 11 years. Despite presenting with local aggressive features and frequent nodal involvement, it encompasses an excellent prognosis. The risk of malignant transformation of congenital melanocytic nevi varies widely accordingly to the projected adult size, number, and concomitant abnormalities found in the central nervous system. The surveillance and treatment of melanoma arising in a congenital melanocytic nevus is challenging, enclosing poor outcomes. In adolescents, the most common subtype is the conventional (adult-type). Contrary to the adult population, the majority of conventional pediatric melanoma arises from previous nevi but follows the general adult epidemiology and risk factors. Specific guidelines for management of pediatric melanoma do not exist and it is treated similarly to melanoma in the adult.